Organocatalytic Asymmetric Desymmetrization of 2,5-Cyclohexadienones: From Single-Bond Formation to Domino Reactions - Sharma, Manisha; Sodhi, Vanisha; Sharma, Pragati; Chauhan, Pankaj (Synlett, 2025)
The enantioselective desymmetrization of prochiral and meso-compounds represents a powerful strategy for constructing complex, stereochemically enriched molecules from simple precursors. Among these, 2,5-cyclohexadienones have emerged as highly versatile substrates due to their inherent prochirality, electronic polarization toward nucleophiles, and the feasibility of diverse functionalization at the C4 position. While early advances in this area were largely limited to intramolecular organocatalytic desymmetrizations—particularly via Michael-type additions—recent efforts have begun to explore the untapped potential of intermolecular and domino processes. This account details our group’s contributions to the development of organocatalytic transformations that enable the enantioselective desymmetrization of 2,5-cyclohexadienones, ranging from single bond-forming reactions to complex domino sequences.
Keywords: Organocatalysis; Asymmetric synthesis; Desymmetrization Reactions; Domino reaction; 2,5-Cyclohexadienones